Knowledge Management : A Tool For Organizational Reforms In The 21st Century - Sung, Foo Chung (2002)
The thesis is about a new set of foundations for amangement methods. Specifically, it is about what knowledge is, and how business can use it, harness, enhance, and manage it so it is of the best value to the organization.